The ECB’s Evolving Mandate and High Independence: An Undemocratic Mix - Anna-Lena Högenauer; Joana Mendes (Politics and Governance)
After over a decade of crisis, the ECB’s functions have expanded considerably. The ECB’s activities during the eurozone crisis, new debates on the ECB’s role in supporting political goals like the fight against climate change, and its participation in geopolitical stand-offs have overcome the fiction of a technocratic role that can be allocated to an independent institution with few constraints to democracy. We highlight how the ECB’s mandate has been (re)interpreted while eschewing the impact of this change on its independence. Drawing on the contributions to this thematic issue, we also argue that the limited legal and political accountability does not match the evolving mandate. In particular, we contrast the voluntary mechanisms of accountability created in the past years and the judicial endorsement of the expansion of the ECB’s mandate.